Methylparaben and ethylparaben exposure through breast milk in the first six months of lactation: A Taiwanese cohort study with estimated daily intake for breastfed infants - Ting Chang; Ching-Chung Tsai; Ting-I Lin; Hsien-Kuan Liu; Jau-Ling Suen; San-Nan Yang; Chien-Yi Wu; Pei-Ling Wu; Yung-Ning Yang (Food and Chemical Toxicology, 2026)

Real-world emission factors and inhalation health risks of PM-bound metals from workboats using ultra-low sulfur marine fuel - Po-Yen Chien; Chia-Hsiang Lai; Chia C. Wang; Dhruv Vishal Patel; Ajay Pillarisetti; Wu-Xing Chen; Chia-Hung Chen; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Dong-Ni Wu; I-Hsuan Wu; et al. (Environmental Pollution, 2026)

Single-cell transcriptomics reveal PRRC1 as a malignant cell enriched driver of DNA repair and therapy resistance in glioblastoma - Sachin Kumar; Ming-Cheng Tsai; Dahlak Daniel Solomon; Juan Lorell Ngadio; Do Thi Minh Xuan; Ching-Chung Ko; Hung-Yun Lin; Meng-Chi Yen; I-Jeng Yeh; Yung-Kuo Lee; Hui-Ru Lin; Jian-Ying Chuang; et al. (DNA Repair, 2026)

Classification of 14 major meteoroid streams based on long-term population indices of their meteor showers - Chih-Ming Lin; I-Ching Yang (Planetary and Space Science, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

The characteristics of the distribution of meteor beginning heights in Quadrantids, Perseids and Geminids - Chih-Ming Lin; I-Ching Yang (Advances in Space Research, 2026)

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Quantification of the variability of the soil moisture field in response to variations in the rainfall field - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee; Wei-Cheng Lo (Journal of Hydrology, 2025)

Characterization of temporal nonstationary random soil moisture perturbation fields - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee; Wei-Cheng Lo (Advances in Water Resources, 2025)

Mechanistic insights into capacitive ion exchange for selective divalent ion removal using activated carbon electrodes - Ming-Han Tsai; Shu-Ju Chao; David Chiuni Wang; I-Hsuan Lin; Li-Ching Chung; Po-I Liu; Lap-Cuong Hua; Hung-Yi Huang; Chi-Chang Hu (Chemical Engineering Journal, 2025)

Antimony induces mitochondria-dependent and ER stress-triggered apoptosis via the oxidative stress-activated JNK signaling pathway in pancreatic islet β-cells - Ken-An Lin; Chin-Chuan Su; Shing-Hwa Liu; Kuan-I. Lee; Kai-Min Fang; Chih-Hsin Tang; Chun-Ying Kuo; Kai-Chih Chang; Jun-An Ke; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology, 2025)

Prenatal exposure to air pollution and pediatric acute leukemia: A nationwide study - Hsin-Chien Yen; I-Chieh Chen; Wei-Szu Lin; Kuan-Chia Lin; Meng-Che Wu; Ching-Heng Lin (Science of The Total Environment, 2025)

3D printed microtissue cassettes enabling high throughput proton radiobiological assays - Chih-Tsung Yang; I-Chun Cho; Ching-Fang Yu; Edward Cheah; Tesi Liu; Yi-Ping Lin; Sing-Yu Hu; Jyun-Wei Jheng; Ivan Kempson; Tsi-Chian Chao; Sen-Hao Lee; Eva Bezak; et al. (Analytica Chimica Acta, 2025)

The herbicide 2,4-dichlorophenoxyacetic acid induces pancreatic β-cell death via oxidative stress-activated AMPKα signal downstream-regulated apoptotic pathway - Ken-An Lin; Chin-Chuan Su; Kuan-I Lee; Shing-Hwa Liu; Kai-Min Fang; Chih-Hsin Tang; Wei-Cheng Lia; Chun-Ying Kuo; Kai-Chih Chang; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology Letters, 2025)

Spatial variability of groundwater flow fields caused by nonstationary random input parameter processes - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee (Journal of Hydrology, 2025)

Artificial digestion represents the worst-case scenario for studying nanoplastic fate in gastrointestinal tract - Giselle Lee; Ya-Jhu Jhang; Yu-Tung Jhang; Yen-Chen Chang; Hui-Wen Chang; Chun-Yu Chuang; Yung-Kun Chuang; Ching-Wei Lin; I-Lun Hsiao (Journal of Hazardous Materials, 2025)

Dual functionality of carbazole-based phosphonic acid molecular additives realizes efficient hole transport layer-free perovskite light-emitting diodes - Yin-Ti Lai; Chiung-Han Chen; Ming-Hsuan Yu; Hsing-Yu Kuo; I-Chih Ni; Bi-Hsuan Lin; Hobeom Kim; Chi-Ching Kuo; Yu-Jung Lu; Chu-Chen Chueh (Chemical Engineering Journal, 2025)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Kaguacidine A: a novel spirohydantoin-containing cucurbitane glycoside from vines of Momordica charantia L. - Hung-Tse Huang; I-Wen Lo; Yu-Chi Lin; Liao Geng-You; Yun-Sheng Lin; Li-Jie Zhang; Tsung-Lin Li; Chia-Ching Liaw; Yao-Haur Kuo (Natural Product Research, 2024)

Protective Effects of Roselle Aqueous Extracts against UV-Induced Damage in Zebrafish Fins - I-Ting Lee; Ching-Yuan Huang; Wei-Lin Su; Tran M. Truong; Chi-Chung Wen; Bo-Chang Wang; Yau-Hung Chen (Fishes, 2024)
(1) Background: Roselle (Hibiscus sabdariffa) is a flowering plant reported to have anti-obesity, antioxidant, antibacterial, and anti-inflammatory effects. This study aims to evaluate the UV-absorbing and antioxidant activities of roselle aqueous extracts (RAE) and test the protective effects of RAE against UV radiation in zebrafish embryos. (2) Methods: DPPH assay and UV-spectrum methods were applied to evaluate the antioxidant and UV-absorbing activities, respectively. The protective effects of RAE were evaluated using fin morphology recording, Kaplan–Meier analysis, and Cox proportional hazards regression. Real-time PCR experiments were also applied to detect both the UV- and RAE-induced gene expressions. (3) Results: Our results show that (i) RAE had UV-absorbing abilities and significantly reduced ROS production in vitro; (ii) the mean times of malformed fins in the UV + RAE (36 and 48 ppm) groups were 3.56 and 4.44 days, respectively, and were prolonged compared to those in the UV-only group (3.36 days); (iii) zebrafish in the UV + RAE (36 and 48 ppm) groups were 0.963 and 0.496 (p

Quantifying payloads of antibody‒drug conjugates using a postcolumn infused-internal standard strategy with LC‒MS - Chih-Ning Cheng; Hsiao-Wei Liao; Ching-Hung Lin; Wen-Chi Chang; I-Chun Chen; Yen-Shen Lu; Ching-Hua Kuo (Analytica Chimica Acta, 2024)

Stochastic Quantification of Spatial Variability of Flow Fields in Heterogeneous, Non-uniform, Confined Aquifers - Chuen-Fa Ni; Ching-Min Chang; Chi-Ping Lin; I-Hsian Lee (Transport in Porous Media, 2024)

Variability in the displacement of solute particles in heterogeneous confined aquifers - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee (Advances in Water Resources, 2024)

Photo-protection and photo-inhibition during light induction in Barbula indica and Conocephalum conicum under different light gradients - Chung-I. Chen; Kuan-Hung Lin; Meng-Yuan Huang; Kuei-Yu Yao; Chau-Ching Huang; Tzu-Chao Lin; En-Liang Chu; Jia-Dong Yang; Ching-Wen Wang (Photosynthesis Research, 2024)

Deciphering microbial communities and their unique metabolic repertoire across rock-soil–plant continuum in the Dayoukeng fumarolic geothermal field of the Tatun Volcano Group - Jung-Sheng Chen; Bashir Hussain; Hsin-Chi Tsai; Viji Nagarajan; Rajendran Senthil Kumar; I-Ching Lin; Bing-Mu Hsu (Environmental Science and Pollution Research, 2023)

Variability of travel time of solute particles in single fractures with spatially variable aperture - Ching-Min Chang; Chuen-Fa Ni; Chi-Ping Lin; I-Hsian Lee (Engineering Geology, 2023)

Dynamic total factors’ environmental efficiency in European union countries - Ching-Cheng Lu; Yung-ho Chiu; I-Fang Lin; Tai-Yu Lin (Environment, Development and Sustainability, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Two-stage dynamic data envelopment analysis measuring the overall efficiency and productivity changes of industry and agriculture in EU countries - Ching-Cheng Lu; I-Fang Lin; Tai-Yu Lin; Yung-ho Chiu (Journal of Cleaner Production, 2023)

Stochastic analysis of the variability of groundwater flow fields in heterogeneous confined aquifers of variable thickness - Ching-Min Chang; Chuen-Fa Ni; We-Ci Li; Chi-Ping Lin; I-Hsian Lee (Stochastic Environmental Research and Risk Assessment, 2022)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Genetic Deletion of Soluble Epoxide Hydroxylase Causes Anxiety-Like Behaviors in Mice - Hsueh-Te Lee; Kuan-I Lee; Hui-Ching Lin; Tzong-Shyuan Lee (Molecular Neurobiology, 2019)

Prevalence, mechanisms and genetic relatedness of the human pathogenic fungus Aspergillus fumigatus exhibiting resistance to medical azoles in the environment of Taiwan - Hsuan‐Chen Wang; Jui‐Chang Huang; Yong‐Hong Lin; Yu‐Hsin Chen; Ming‐I Hsieh; Pui‐Ching Choi; Hsiu‐Jung Lo; Wei‐Lun Liu; Ching‐Shan Hsu; Hsin‐I Shih; Chi‐Jung Wu; Yee‐Chun Chen (Environmental Microbiology, 2018)
Summary Emerging azole resistance in Aspergillus fumigatus poses a serious threat to human health. This nationwide surveillance study investigated the prevalence and molecular characteristics of azole‐resistant A. fumigatus environmental isolates in Taiwan, an island country with increasing use of azole fungicides. Of the 2760 air and soil samples screened from 2014 to 2016, 451 A. fumigatus isolates were recovered from 266 samples and 34 isolates from 29 samples displayed resistance to medical azoles (itraconazole, voriconazole or posaconazole). The resistance prevalence was 10.9% and 7.5% in A. fumigatus ‐positive samples and isolates respectively. Most (29, 85.3%) azole‐resistant isolates harboured TR 34 /L98H mutations, which were widely distributed, clustered genetically with clinical isolates, and had growth rates that were similar to those of the wild‐type isolates. Microsatellite genotyping revealed both the global spread of the TR 34 /L98H isolates and the occurrence of TR 34 /L98H/S297T/F495I isolates belonging to local microsatellite genotypes. AfuMDR3 and atrF , two efflux transporter genes, were constitutively upregulated in two individual resistant isolates without cyp51A mutations, highlighting their potential roles in azole resistance. These results emphasize the need for periodic environmental surveillance at the molecular level in regions in which azole fungicides are applied, and agricultural fungicide management strategies that generate less selective pressure should be investigated.

Alleviation of N-Methyl-d-Aspartate Receptor-Dependent Long-Term Depression via Regulation of the Glycogen Synthase Kinase-3β Pathway in the Amygdala of a Valproic Acid-Induced Animal Model of Autism - Han-Fang Wu; Po See Chen; Yi-Ju Chen; Chi-Wei Lee; I-Tuan Chen; Hui-Ching Lin (Molecular Neurobiology, 2017)

Loss of Transient Receptor Potential Ankyrin 1 Channel Deregulates Emotion, Learning and Memory, Cognition, and Social Behavior in Mice - Kuan-I Lee; Hui-Ching Lin; Hsueh-Te Lee; Feng-Chuan Tsai; Tzong-Shyuan Lee (Molecular Neurobiology, 2017)

Identification of susceptibility gene associated with female primary Sjögren’s syndrome in Han Chinese by genome-wide association study - I-Wen Song; Hsiang-Cheng Chen; Yuh-Feng Lin; Jenn-Hwai Yang; Chi-Ching Chang; Chung-Tei Chou; Ming-Ta Michael Lee; Yi-Chun Chou; Chien-Hsiun Chen; Yuan-Tsong Chen; Chen-Hung Chen; Jer-Yuarn Wu (Human Genetics, 2016)

The relationship between plasma and urinary 8-hydroxy-2-deoxyguanosine biomarkers measured by liquid chromatography tandem mass spectrometry - Chung-Ching Wang; Wei-Liang Chen; Chien-Ming Lin; Ching-Huang Lai; Ching-Hui Loh; Hong-I Chen; Saou-Hsing Liou (Environmental Science and Pollution Research, 2016)

Maternal exposure to di-(2-ethylhexyl) phthalate exposure deregulates blood pressure, adiposity, cholesterol metabolism and social interaction in mouse offspring - Kuan-I Lee; Chin-Wei Chiang; Hui-Ching Lin; Jin-Feng Zhao; Cheng-Ta Li; Song-Kun Shyue; Tzong-Shyuan Lee (Archives of Toxicology, 2016)

Avian reovirus S1133-induced apoptosis is associated with Bip/GRP79-mediated Bim translocation to the endoplasmic reticulum - Ping-Yuan Lin; Hung-Jen Liu; Ching-Dong Chang; Yo-Chia Chen; Chi-I Chang; Wen-Ling Shih (Apoptosis, 2015)

Hyperinakin, a new anti-inflammatory phloroglucinol derivative from Hypericum nakamurai - Yuan-Bin Cheng; Ahmed Eid Fazary; Yu-Chi Lin; I-Wen Lo; Seow-Chin Ong; Shun-Ying Chen; Ching-Te Chien; Yen-Jung Lin; Wan-Wan Lin; Ya-Ching Shen (Natural Product Research, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

Transcriptional analysis and functional characterization of XCC1294 gene encoding a GGDEF domain protein in Xanthomonas campestris pv. campestris - Yi-Min Hsiao; Wan-Ling Song; Chao-Tsai Liao; I-Hsuan Lin; Mei-Ying Pan; Ching-Fen Lin (Archives of Microbiology, 2012)

Avian reovirus S1133-induced DNA damage signaling and subsequent apoptosis in cultured cells and in chickens - Ping-Yuan Lin; Hung-Jen Liu; Ching-Dong Chang; Chi-I Chang; Jue-Liang Hsu; Ming-Huei Liao; Jeng-Woei Lee; Wen-Ling Shih (Archives of Virology, 2011)

Analysis of genetic variations in the dopamine D1 receptor (DRD1) gene and antipsychotics-induced tardive dyskinesia in schizophrenia - I-Ching Lai; Geng-Han Mo; Mao-Liang Chen; Ying-Chieh Wang; Jen-Yeu Chen; Ding-Lieh Liao; Ya-Mei Bai; Chao-Cheng Lin; Tzu-Ting Chen; Ying-Jay Liou (European Journal of Clinical Pharmacology, 2011)

An engineering intervention resulting in improvement in lung function and change in urinary 8-hydroxydeoxyguanosine among foundry workers in Taiwan - Ming-Hsiu Lin; Saou-Hsing Liou; Ching-Wen Chang; I-Hsiao Huang; Paul T. Strickland; Ching-Huang Lai (International Archives of Occupational and Environmental Health, 2011)

Point patterns of tree distribution determined by habitat heterogeneity and dispersal limitation - Yi-Ching Lin; Li-Wan Chang; Kuoh-Cheng Yang; Hsiang-Hua Wang; I-Fang Sun (Oecologia, 2011)

Pravastatin attenuates carboplatin-induced cardiotoxicity via inhibition of oxidative stress associated apoptosis - Ching-Feng Cheng; Shu-Hui Juan; Jin-Jer Chen; Ying-Chi Chao; His-Hsien Chen; Wei-Shiung Lian; Chun-Yi Lu; Chung-I Chang; Ted-H Chiu; Heng Lin (Apoptosis, 2008)

Characterization of a novel T4-type Stenotrophomonas maltophilia virulent phage Smp14 - Chiy-Rong Chen; Ching-Hsuan Lin; Juey-Wen Lin; Chi-I Chang; Yi-Hsiung Tseng; Shu-Fen Weng (Archives of Microbiology, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

A fine physical map of the rice chromosome 5 - Chia-Hsiung Cheng; Mei-Chu Chung; Shu-Mei Liu; Shi-Kuang Chen; Fang-Yi Kao; Shu-Jen Lin; Shin-Hsin Hsiao; I-Chieh Tseng; Yue-Ie C. Hsing; Hong-Pang Wu; Ching-San Chen; Jei-Fu Shaw; et al. (Molecular Genetics and Genomics, 2005)

Establishment of red fluorescent protein-tagged HeLa tumor metastasis models: Determination of DsRed2 insertion effects and comparison of metastatic patterns after subcutaneous, intraperitoneal, or intravenous injection - Jau-Yeong Lu; Hui-Chun Chen; Ricky Yuan-Yuan Chu; Tsu-Chun Emma Lin; Ping-I Hsu; Ming-Shyan Huang; Ching-Jiunn Tseng; Michael Hsiao (Clinical & Experimental Metastasis, 2003)

High polyphenol oxidase activity and low titratable acidity in browning bamboo tissue culture - Li-Chun Huang; Ya-Lin Lee; Bau-Lian Huang; Ching-I Kuo; Jei-Fu Shaw (In Vitro Cellular & Developmental Biology - Plant, 2002)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)